Pharmacokinetics and Biodistribution of Zinc-Enriched Yeast in Rats - Shuangqing Zhang; Yan Zhang; Ning Peng; Haibo Zhang; Juan Yao; Zhihong Li; Liegang Liu (The Scientific World Journal)
Zinc-enriched yeast (ZnY) and zinc sulfate (ZnSO4) are considered zinc (Zn) supplements currently available. The purpose of the investigation was to compare and evaluate pharmacokinetics and biodistribution of ZnY and ZnSO4 in rats. ZnY or ZnSO4 were orally administered to rats at a single dose of 4 mg Zn/kg and Zn levels in plasma and various tissues were determined using inductively coupled plasma-optical emission spectrometry. Maximum plasma concentration values were 3.87 and 2.81 μg/mL for ZnY and ZnSO4, respectively. Both ZnY and ZnSO4 were slowly eliminated with a half-life of over 7 h and bone had the highest Zn level in all tissues. Compared to ZnSO4, the relative bioavailability of ZnY was 138.4%, indicating that ZnY had a significantly higher bioavailability than ZnSO4.